Clock It: Solving the 3‑D Chirality Problem with a 2‑D MethodA Simple Algorithm for Teaching and Determining Enantiomers in General Chemistry - Juszczak, Laura J (Journal of chemical education, 2021)
One of the more difficult concepts introduced in the first-year undergraduate course, general chemistry, is that of chirality. Typically, left and right hands are the common, macroscopic objects of reference used to demonstrate the quality of being nonsuperimposable, followed by the use of a mirror and molecular models, to illustrate molecular enantiomers. While this approach works well as an introduction, and the handedness model becomes more useful in organic chemistry where absolute R- and S-configuration assignment becomes necessary, it does not help the general chemistry student to determine molecular chirality or “handedness” at this basic level. Much of the difficulty stems from the representation of 3-dimensional (3-D) structures on the 2-dimensional (2-D) paper plane. While detailed flowcharts exist for molecules of varying orbital hybridization and geometry, these are more suited to advanced students in inorganic chemistry and are not designed to be mentally retained or learned. Additionally, the process of determining R- and S-configurations for carbon tetrahedral centers in organic chemistry is more complex as ligands must be ranked according to Cahn–Ingold–Prelog (CIP) rules. Previous publications have addressed this topic thoroughly. A simple method is presented here (called clocking) which introduces the concept of chirality for general chemistry and primes the way for more complex chirality assignments in higher level courses.